Analysis of Barriers Implementation Health Information Technology Using Vosviewer: A Bibliometric Study - Latifah Mutiara Haryanto; Winny Setyonugroho; Passakorn Suanrueang (Universitas Muhammadiyah Yogyakarta, 2023)
Information technology is growing rapidly in various fields, especially in health services. The development of information technology in health services is e-health, which aims to improve public health, expand and reach health services, and manage patients in real-time. This study aims to determine the publication trend of articles on barriers to medical technology implementation from 2015 – 2022. The publications were retrieved through a search through the Scopus database and obtained 422 publications. This study analyzed the number of publications per year, document type, most contributing countries, subject area of publication, influential authors, number of article citations, and contributing search sources. This study also analyzed and collated documents with Vos Viewer. The results showed that the trend of publications has increased the number of publications from year to year. The types of papers published with the highest number were articles (322 publications) and reviews (90 publications). The most contributing country was the United States, with 191 reports. The dominant subject area was medicine, at 66.23%. The publication with the most citations was an article by Scott Kruse et al. entitled “Evaluating Barriers to Adopting Telemedicine Worldwide: A Systematic Review” from the Journal of Telemedicine and Telecare, with the subject area of medicine having 413 citations. Researchers with the highest number of publications (3) were ten authors. The study was limited by the search for literature from a single database, which allowed the literature to not cover all of the literature on barriers to medical technology implementation.